PENGARUH PERMAINAN EDUKATIF TERHADAP PERKEMBANGAN KOGNITIF ANAK PRA-SEKOLAH DI TAMAN KANAK-KANAK PERTIWI BRAJA EMAS 2025 - Refi Mariska; Nita Evrianasari; Ike Ate Yuviska; Anggraini Anggraini (Universitas Malahayati Bandar Lampung, 2026)
Background: The cognitive development of preschool children remains a significant issue. WHO data indicates that more than 200 million children worldwide do not reach their optimal cognitive potential, with the rate of delay in Indonesia reaching 13–18%. In Lampung Province, only 26.38% of preschool-aged children undergo developmental screening. A similar situation is seen at Pertiwi Braja Emas Kindergarten, where some children still have difficulty recognizing letters and writing.Objective: To determine the effect of educational games on the cognitive development of preschool children.Methods: The study used a pre-experimental, one-group pretest–posttest design with a quantitative approach. The population consisted of 54 respondents, with a sample size of 30 children aged 5–6 years selected using a purposive sampling technique. The research instruments consisted of Standard Operating Procedures (SOPs) for puzzle games and observation sheets. Univariate and bivariate data analysis used the Wilcoxon Signed Rank Test.Results: the study showed that the average cognitive development score of children before educational play was 49.20, increasing to 72.43 after educational play. The statistical test using the Wilcoxon test yielded a p- value of 0.000 (p-value α=0.05).Conclusion: That educational play has an effect on cognitive development in preschool children at Braja Emas 2025 Kindergarten.Recommendation: Teachers are expected to continue to increase the use and variety of educational games in daily learning. Keywords: Educational Games, Cognitive Development, Preschool ABSTRAK Latar Belakang: Perkembangan kognitif anak prasekolah masih menjadi masalah penting. Data WHO menyebutkan lebih dari 200 juta anak di dunia tidak mencapai potensi kognitif optimal, dengan angka keterlambatan di Indonesia 13–18%. Di Provinsi Lampung hanya 26,38% anak usia prasekolah yang menjalani deteksi tumbuh kembang. Kondisi serupa terlihat di TK Pertiwi Braja Emas, di mana beberapa anak masih kesulitan mengenal huruf dan menulis.Tujuan: Diketahui pengaruh permainan edukatif terhadap perkembangan kognitif anak prasekolah.Metode: Jenis penelitian menggunakan desain pra-eksperimental one group pretest–posttest dengan pendekatan kuantitatif. Populasi sebanyak 54 responden dengan sampel berjumlah 30 anak usia 5–6 tahun yang dipilih dengan teknik purposive sampling. Instrumen penelitian berupa Standar Operasional Prosedur permainan puzzle dan lembar observasi. Analisis data univariat dan bivariat dengan menggunakan uji Wilcoxon Signed Rank Test.Hasil: Sebelum bermainan edukatif rata-rata skor perkembangan kognitif anak adalah 49,20 meningkat menjadi 72,43 setelah bermainan edukatif. Hasil uji statistik menggunakan uji Wilcoxon nilai p-value = 0,000 (p- value a=0,05).Kesimpulan: Ada pengaruh permainan edukatif dengan perkembangan kognitif pada anak pra-sekolah di taman kanak-kanak Braja Emas 2025.Saran: Guru diharapkan terus meningkatkan penggunaan dan variasi permainan edukatif dalam proses pembelajaran sehari-hari. Kata Kunci: Permainan Edukatif, Perkembangan Kognitif, Prasekolah.